The Fitch Family: Female Missionaries and Modern China: A Study Centered on the Fei Wusheng Archives Held by the Yanjing Library at Harvard University - FENG, Cui (Journal of Research for Christianity in China (JRCC), 2025)
This study focuses on a female missionary from the Fitch family, an American missionary family that lived and worked in China. Taking the family as its point of entry, it draws upon family historical materials and other relevant documents from the Fei Wu Sheng archives held at Harvard University’s Yenching Library. The research unfolds the interactions and mutual reinforcement among the female missionary, her family, her personal life, and her missionary work in China across three levels: a single family, a group of women, and a typical case.